2014
DOI: 10.1111/jhq.12002
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Hospital-Onset Clostridium difficile Infection in the New York Metropolitan Region Using a Collaborative Intervention Model

Abstract: The incidence, severity, and associated costs of Clostridium difficile (C. difficile) infection (CDI) have dramatically increased in hospitals over the past decade, indicating an urgent need for strategies to prevent transmission of C. difficile. This article describes a multifaceted collaborative approach to reduce hospital-onset CDI rates in 35 acute care hospitals in the New York metropolitan region. Hospitals participated in a comprehensive CDI reduction intervention and formed interdisciplinary teams to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 25 publications
0
34
0
Order By: Relevance
“…Only 2 studies (12%) reported pathogen acquisition as a primary outcome (83, 90). Clinical infection was reported as a primary and secondary outcome in 3 (80, 83, 90) and 2 (75, 76) studies, respectively. With regard to pathogen type, C. difficile and VRE were the primary focus of 3 (75, 80, 81) and 2 (85, 90) studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 2 studies (12%) reported pathogen acquisition as a primary outcome (83, 90). Clinical infection was reported as a primary and secondary outcome in 3 (80, 83, 90) and 2 (75, 76) studies, respectively. With regard to pathogen type, C. difficile and VRE were the primary focus of 3 (75, 80, 81) and 2 (85, 90) studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies (18%) (75, 76, 80) used multicomponent strategies to prevent C. difficile infections and reported positive findings. Five studies (64, 76, 81, 84, 87) reporting on sustainability of preventive strategies described ongoing education, direct feedback, and commitment and flexibility of administrative leaders as key components to successful implementation.…”
Section: Resultsmentioning
confidence: 99%
“…25,28,29 In our baseline scenario, patients who became colonized and diseased within the hospital ward represented, on average, 50% of the possible HO-CDI cases. Those colonized on admission have been considered to be at lower risk for subsequent onset of disease than those not colonized.…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, the frequency of Table 1 Overall incidence of C difficile episodes, incidence in A-ICUs, and incidence in the remaining hospital units [19]. Previous studies have suggested the efficacy of specific infection control measures in reducing the incidence of CDI [20][21][22]. Rapid diagnosis of CDI is essential to improve patient outcome and prevent disease transmission.…”
Section: Discussionmentioning
confidence: 99%